2013
DOI: 10.1002/ijc.28355
|View full text |Cite
|
Sign up to set email alerts
|

Time trends in the prevalence of HPV in oropharyngeal squamous cell carcinomas in northern Spain (1990–2009)

Abstract: Recent studies support an important role for human papillomavirus (HPV) in oropharyngeal squamous cell carcinomas (OPSCC), although the incidence varies widely depending on the geographic location and time period studied. The aim of this study was to determine the proportion of HPV in a large cohort of OPSCC in northern Spain in the years 1990-2009. Clinical records and paraffin embedded tumor specimens of 248 consecutive patients surgically treated for OPSCC (140 tonsillar and 108 base of tongue) between 1990… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
53
2
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 24 publications
(49 reference statements)
3
53
2
2
Order By: Relevance
“…One of the possible explanations for the low proportion may lie in a lower exposure to HPV, either due to a lesser presence of HPV in the general population in the north of Spain or to different sexual behavior. In fact, in a previous study we have also found a very low proportion (3.2%) of HPV-related oropharyngeal squamous cell carcinomas in our region [20]. The high prevalence of tobacco smoking and alcohol drinking in our region could also influence this low proportion of HPV-related HNSCCs.…”
Section: Discussionmentioning
confidence: 49%
“…One of the possible explanations for the low proportion may lie in a lower exposure to HPV, either due to a lesser presence of HPV in the general population in the north of Spain or to different sexual behavior. In fact, in a previous study we have also found a very low proportion (3.2%) of HPV-related oropharyngeal squamous cell carcinomas in our region [20]. The high prevalence of tobacco smoking and alcohol drinking in our region could also influence this low proportion of HPV-related HNSCCs.…”
Section: Discussionmentioning
confidence: 49%
“…The prevalence of HPV-positive OPSCCs shows a considerable geographical variation with reported prevalence ranging from 3.2% in northern Spain12 to 79% in Sweden,13 and a meta-analysis reported a HPV prevalence of 51% 7. We find that 22% of SCCs in the soft palate are HPV-positive, which is lower compared with similar research 6 13.…”
contrasting
confidence: 51%
“…Therefore, a geographic differentiation of the study origin was not necessary. However, in future, as more data are available, such geographic distinctions may become relevant, since tobacco consumption and the incidence of HPV infection show differences between countries and continents [4,10,61]. Cofactors such as smoking behavior may impact the prevalence and presence of the two markers HPV and p16, but not the survival of the distinct subgroups [8,72].…”
Section: Discussionmentioning
confidence: 90%